Le rapport sur le développement de la Banque mondiale : un changement de paradigme en trompe-l’œil - Gilles Van Hamme; Mathieu Van Criekingen; Moritz Lennert (Cybergeo, 2010)
In this note, we explore the question of whether the adoption by the World Bank of a new paradigm of economic space inspired by the new economic geography leads to a new political vision about development. The answer is clearly no: the new focus on agglomeration and macro-regional integration is used to justify exactly the same old liberal policies encouraged by the World Bank for the last thirty years.